(untitled) (Circe de clásicos y modernos, 2018)
Among the various fi n-de-siècle reinterpretations of the ‘decadent’ latin literature, Le latin mystique (1892) of Remy DE GOURMONT has a singular place, because is not only a critical essay but also an annotated and translated anthology. Le latin mystique, book that reviews a literature supposedly not studied by critics and scholars, is a key text for understanding aspects of the fin-de-siècle sensibility and the ‘non-academic’ readings that twentieth century writers, like Ezra POUND or Jorge Luis BORGES, will make of the classical and medieval latin literature.